Potential of Peptides as Inhibitors and Mimotopes: Selection of Carbohydrate-Mimetic Peptides from Phage Display Libraries - Matsubara, Teruhiko (Journal of Nucleic Acids, 2012)
Glycoconjugates play various roles in biological processes. In particular, oligosaccharides on the surface of animal cells are involved in virus infection and cell-cell communication. Inhibitors of carbohydrate-protein interactions are potential antiviral drugs. Several anti-influenza drugs such as oseltamivir and zanamivir are derivatives of sialic acid, which inhibits neuraminidase. However, it is very difficult to prepare a diverse range of sugar derivatives by chemical synthesis or by the isolation of natural products. In addition, the pathogenic capsular polysaccharides of bacteria are carbohydrate antigens, for which a safe and efficacious method of vaccination is required. Phage-display technology has been improved to enable the identification of peptides that bind to carbohydrate-binding proteins, such as lectins and antibodies, from a large repertoire of peptide sequences. These peptides are known as “carbohydrate-mimetic peptides (CMPs)” because they mimic carbohydrate structures. Compared to carbohydrate derivatives, it is easy to prepare mono- and multivalent peptides and then to modify them to create various derivatives. Such mimetic peptides are available as peptide inhibitors of carbohydrate-protein interactions and peptide mimotopes that are conjugated with adjuvant for vaccination.